HISTOPATHOLOGIC FEATURES OF HEPATOPANCREAS INFECTED WITH Vibrio parahaemolyticus IN VANNAMEI SHRIMP (Litopenaeus vannamei) - Wijaya, Avira Salsabila; Insivitawati, Era; Sugianti, Budi (Universitas Mataram, 2025)
Shrimp farming faces a major problem, which is the disease caused by Vibrio parahaemolyticus infection, leading to vibriosis and damage to the shrimp's hepatopancreas. This study aims to analyze the pathological changes that occur in the tissues and organs of vannamei shrimp due to Vibrio parahaemolyticus infection using histopathological testing methods. The research findings show that this bacterial infection causes damage to the hepatopancreas, including hemocyte infiltration, melanization, sloughing, necrosis, and bacterial colonization. This damage is caused by toxins produced by Vibrio parahaemolyticus, leading to the degeneration of cells and tissues. This study provides important information that can be used to develop prevention and treatment strategies for diseases in vannamei shrimp farming, as well as enhance understanding of the impact of bacterial infection on the hepatopancreas organ of shrimp.